Impact of tumour characteristics and cancer treatment on cerebrovascular mortality after glioma diagnosis: Evidence from a population-based cancer registry - Jin, Kai; Brennan, Paul M.; Poon, Michael T. C.; Figueroa, Jonnie D.; Sudlow, Cathie L. M. (Frontiers in Oncology, 2022)
Objective. Brain tumour patients have the highest stroke mortality rates among all cancer types, but the factors associated with fatal stroke remain unknown. We aimed to examine to what extent brain tumour grade, a marker of biological aggressiveness, tumour size and cancer treatment are associated with cerebrovascular mortality among patients with malignant glioma, the most common and aggressive type of brain tumour. Methods. We conducted a retrospective, observational cohort study using the US National Cancer Institute’s state and regional population-based cancer registries (NCI SEER). We identified adult patients with a primary diagnosis of malignant glioma in 2000 to 2018 (N=72,916). The primary outcome of interest was death from cerebrovascular disease. Cox regression modelling was used to estimate the associations with cerebrovascular mortality of tumour grade, tumour size and treatment (surgery, radiotherapy, chemotherapy), calculating hazard ratios (HR) adjusted for these factors as well as for age, sex, race, marital status and calendar year. Results. Higher grade (Grade IV vs Grade II: HR=2.47, 95% CI=1.69-3.61, p<0.001) and larger brain tumours (size 3 to <6 cm: HR=1.40, 95% CI=1.03 -1.89, p<0.05; size ≥ 6 cm: HR=1.47, 95% CI=1.02-2.13, p<0.05 compared to size < 3cm) were associated with increased cerebrovascular mortality. Having cancer treatment was associated with decreased risk (surgery: HR= 0.60, p<0.001; chemotherapy: HR=0.42, p<0.001; radiation: HR= 0.69, p<0.05). However, among patents surviving five years or more from their cancer diagnosis radiotherapy was associated with higher risk of cerebrovascular mortality (HR 2.73, 95% CI 1.49-4.99, p<0.01). Conclusion. More aggressive tumour characteristics are associated with increased cerebrovascular mortality, and treatment was associated with lower risk within 5 years of diagnosis. Radiotherapy increased risk of fatal cerebrovascular outcome five-year after cancer diagnosis. Further research is needed to better understand the long-term cardiovascular consequences of radiation therapy, and whether the consequent risk can be mitigated.